Rancang Bangun Alat Pengujian Focus Film Distance (FFD) - Andrey Nino Kurniawan (Jurnal Imejing Diagnostik (JImeD), 2017)
Background : Focus film distance (FFD) settings may affect the quality of radiograph, such as: density of the film, contrast, the intensity of x-ray radiation, detail and distortion of the image of the object, so that should be done appropriately. However, in practice, focus markers are often not given, lost or covered by accessories in x-ray tubes, so the technologist difficulties in determining the location of the focal point. It will make the technologist in the measurement of FFD done by measuring the approximate location of the focal point to the receptors. And yet there is a special tool that can be used to measure the accuracy of the settings of the FFD.Methods : The research will focus on the design of FFD measurement tools using acrylic materials, copper wire and small iron balls. Research methods is experimental with trial and error design, tool architecture will be done some test functions, include: Test of acrillic material (radiograph image), copper wire alignment test, test of steady ball of iron ball, FFD measure test. Evaluation is done by comparing wire image measurement with mathematical calculation using magnification formula.Results : The results of this research is the formation of FFD testing tool that is made has dimensions of 18 cm x 10 cm x 20 cm using acrillic material wich inside the part there is wire measuring 2 cm, 10 cm, and 16 cm and two iron balls are mutually perpendicular. The function test of the device is obtained as follows: the test of acrilic material in the radiographic image has been able to distinguish the acrylic material with wire and iron ball so as not to interfere with the measurement of the length of the wire image; copper wire alignment test found that the position of each wire mounted on plate A is aligned and is 20 cm from the bottom of the tool; the steady iron ball deformity test on plate A and plate B is straight-forward